Modification in Antioxidant Potential of Coriandum sativum Using Selected Plant Growth Regulators - Aslam, Maryam; Sultana, Bushra; Ali, Shaukat (Asian Journal of Chemistry, 2014)
Plant growth regulators were employed on coriander (Coriandum sativum) to evaluate their possible effects on total phenolic content and antioxidant attributes. Applied plant growth regulators were humic acid, Moringa leaf extract, 6-benzyl amino purine in foliar and bio-fertilizer and humic acid in seed priming mode at varying dose rate. The treatments were applied in two soil environment, urea presence (experiment A) and urea absence (experiment B). The observed total phenolic content variations ranged as: 2.929-10.156 mg GAE/g of DM, reducing power estimated as: 0.613-1.952 (at 10.00 mg/mL extract concentration) while DPPH• scavenging ability as: 0.354-0.979 μg/mL. Moringa leaf extract excelled in total phenolic content and DPPH• assay, while, bio-fertilizer remained dominated in reducing power assay. Overall experiment A showed improved results than experiment B. Antioxidant activity was found to be enhanced significantly (P < 0.05) with exogenously applied treatments of plant growth regulators. However, Moringa leaf extract showed comparatively improved effects.